Best methods of improving soils - Rogler, Henry William (My University, 1898)
Introduction: When our fore-fathers landed here, they found a soil rich in organic matter and all kinds of plant food ready to respond to any kind of cultivation. They made little or no attempt to retain the natural wealth of the soil and the phrase “inexhaustible fertility” was a common one. Little did they think that soil improvement would become a question of paramount important to coming generations. When settlers came to Kansas the valleys were covered with dense growth of grass, together with large quantities of ashes and mold which had accumulated for years and when the old fashioned breaking plow first turned a furrow the ground was found black and deep and filled with those elements which make the difference between a fertile and infertile soil. Under such conditions it was natural to heed very little rotation on any other method of natural or artificial improvements so common and necessary today.
Citation: Rogler, Henry William. Best methods of improving soils. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Soil; Fore-fathers; Cultivation; Kansas; Valleys; Grass; Theses; Manuscripts (documents)